1994
DOI: 10.1111/j.1440-1681.1994.tb02459.x
|View full text |Cite
|
Sign up to set email alerts
|

High Fish Oil Diet Increases Oxidative Stress Potential in Mammary Gland of Spontaneously Hypertensive Rats

Abstract: 1. The purpose of this study was to determine whether high omega-3 (19% menhaden oil, 1% corn oil) or high omega-6 (20% corn oil) fatty acid diets would decrease expression of hypertension in the female spontaneously hypertensive rat (SHR), promote tumourigenesis in the rat 7,12-dimethylbenz[a]anthracene (DMBA) model of mammary cancer or increase the susceptibility of the mammary gland to lipid peroxidation. A group of rats on a 5% corn oil diet served as the low fat control group. 2. We found that the high om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The fatty acid profiles of the diets used in our study (Table 3) are similar to profiles in the literature for both herring and maize oil (Stansby, 1969(Stansby, , 1986Mehta et al 1994). A profile for pollock oil was not found.…”
Section: Diet Qualitysupporting
confidence: 81%
See 1 more Smart Citation
“…The fatty acid profiles of the diets used in our study (Table 3) are similar to profiles in the literature for both herring and maize oil (Stansby, 1969(Stansby, , 1986Mehta et al 1994). A profile for pollock oil was not found.…”
Section: Diet Qualitysupporting
confidence: 81%
“…Efficiency of energy utilization was calculated as the weight gain over 9 weeks, divided by the energy intake (Harris, 1991;Mehta et al 1994;Iossa et al 1997); protein efficiency ratio was calculated as the weight gain over 9 weeks divided by the amount of protein consumed (Muller & Tobin, 1980).…”
Section: Efficiency Of Energy Utilization and Protein Efficiency Ratiomentioning
confidence: 99%
“…The degree of lipid peroxidation is proportional to the number of double bonds in unsaturated fatty acids ( 1 ) . The observation that MCT diet-fed piglets had lower hepatic MDA concentrations than SO diet-fed piglets supports the findings of Diniz et al ( 43 ) , who reported that the ratio of PUFA:SFA in diets played an important role in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…They can form organic free radicals, causing a cascade of damages to endogenous lipids and oxidative stress ( 2 , 3 ) . In fact, a positive correlation has been observed between the amounts of dietary PUFA and the extent of lipid peroxidation ( 1 ) .…”
mentioning
confidence: 99%
“…The Western diet generally includes at least 30-40% of energy as fat, and a typical American diet is 20% fat, resulting in a 40% energy intake from fat [1]. Current recommendations are to lower dietary fat and calories, but a dietary change often results in high carbohydrate and high protein diets.…”
Section: Introductionmentioning
confidence: 97%